Agro-process intensification: soilborne micro-bioreactors with nitrogen fixing bacterium Azospirillum brasilense as self-sustaining biofertiliser source for enhanced nitrogen uptake by plants - Akay Galip; Fleming Steven (Green Processing and Synthesis, 2012)
A new application of agro-process intensification is described for nitrogen fixation by Azospirillum brasilense supported within the pores of sulphonated-neutralised polyHIPE polymers (PHPs) which are highly hydrophilic, elastic, crosslinked and ionic with nano-structured pore walls. These bioactive macroscopic polymer particles, when used as soil additives act as micro-bioreactors within the soil and facilitate the interactions between plant roots, root exudates, water, nutrients and bacteria (reactive components), because plant roots penetrate into these micro-bioreactors which simultaneously absorb water and nutrients while generating biofertiliser through the nitrogen fixing bacteria within them. Hence, these soil additives act as synthetic rhizosphere (SRS). In greenhouse experiments, it is shown that the presence of the bioactive SRS at 0.5 wt% level in the soil without any fertiliser addition increases the dry grass shoots by 9.6%, 9.5%, 40% and 145% after 3, 6, 9 and 12 weeks of growth, respectively, compared to grass grown with no SRS or bacteria. Progressive yield enhancement with Azospirillum brasilense supported on PHPs is due to reduction of soil nutrients thus switching nitrogen fixing bacterium from consumption to production of nitrogen. The environmental impact and sustainability of SRS media are also considered and compared with other soil additives: super absorbent polymers and biochar.